Improving The Activities Of Learning And Writing The Poetry Of Class Viii Students In Smp Negeri 23 Oku Through Contextual Approaches - Herlina, Lilian; Missriani, Missriani; Fitriani, Yessi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to increase learning activities and writing poetry by using a contextual approach to class VIIIA students of SMP Negeri 23 OKU. The method used is the descriptive quantitative method. Data in the form of poetry writing tests are classified as quantitative data and data in the form of observations are classified as qualitative data. Based on the results of data analysis of student learning outcomes applied in writing poetry using a contextual approach, it was found that the increase in student learning activities in cycle I was 65.45%, cycle II was 81.21%, and cycle III was 96.36%. The activities of implementing contextual learning in cycle I am effective categories, cycle II are effective categories, and cycle III are very effective categories. The learning activities carried out by the teacher were based on observer observations, namely cycle I was 75.65%, cycle II was 80% and cycle III was 96.25%. The improvement also occurred in the results of writing poetry that had been done by students through the test, namely the pre-cycle average score of 60.45; cycle I average value of 67.73; cycle II the average value of 73.73; and cycle III with an average value of 80.09. The number of students and the percentage of completeness is in the pre-cycle a number of 8 students with a percentage of 24.24%; cycle I a number of 21 students with a percentage of 63.64%; cycle II a total of 26 students with a percentage of 78.79%; and the third cycle of 33 students with a percentage of 100%. Thus, the use of a contextual approach to learning to write poetry can increase the activity and learning outcomes of class VIIIA students of SMP Negeri 23 OKU.